Initiatives to reduce nonprescription sales and dispensing of antibiotics: Findings and implications - Vanda Markovic-Pekovic; Nataša Grubiša; Johanita Burger; Ljubica Bojanić; Brian Godman (Wolters Kluwer Medknow Publications, 2017)
Objective: Irrational use of antimicrobials is a major driver of antimicrobial resistance, exacerbated by dispensing antibiotics without a prescription. Our previous study suggested this was a problem in the Republic of Srpska despite legislation. Since then, a number of activities have been initiated. Consequently, the study aimed to ascertain whether these multiple initiatives had reduced this. Methods: Patients visiting all community pharmacies in the Republic from October 2014 to July 2015 presenting with symptoms typical of an acute, viral, and mostly uncomplicated upper respiratory tract infection, with results compared to the previous study. If an antibiotic was suggested, the maximum allowance was €3/pack. Findings: Self-medication with antibiotics significantly decreased from 58% to 18.5% of pharmacies. In both studies, most patients were offered over-the-counter medication. The most common reason for not dispensing an antibiotic was "antibiotics can be dispensed with a prescription only." The penicillins were the most dispensed antibiotic. Fewer patients than the previous study were given instructions about antibiotic use and no discussion on their side effects. Conclusion: While encouraging that self-medication decreased significantly, 18.5% were disappointing given recent initiatives. Fewer instructions about antibiotics if an antibiotic was dispensed were also disappointing. This suggests the need for even stronger enforcement of the laws as well as further training of pharmacy personnel to ensure the future appropriate use of medicines.